Argininosuccinate synthase 1 (ASS1): A marker of unclassified hepatocellular adenoma and high bleeding risk. Issue 6 (30th October 2017) - Henriet, Elodie; Abou Hammoud, Aya; Dupuy, Jean‐William; Dartigues, Benjamin; Ezzoukry, Zakaria; Dugot‐Senant, Nathalie; Leste‐Lasserre, Thierry; Pallares‐Lupon, Nestor; Nikolski, Macha; Le Bail, Brigitte; Blanc, Jean‐Frédéric; Balabaud, Charles; et al.
Abstract : Hepatocellular adenomas (HCAs) are rare benign tumors divided into three main subgroups defined by pathomolecular features, HNF1A (H‐HCA), mutated β‐catenin (b‐HCA), and inflammatory (IHCA). In the case of unclassified HCAs (UHCAs), which are currently identified by default, a high risk of bleeding remains a clinical issue. The objective of this study was to explore UHCA proteome with the aim to identify specific biomarkers. Following dissection of the tumoral (T) and nontumoral (NT) tissue on formalin‐fixed, paraffin‐embedded HCA tissue sections using laser capture methodology, we performed mass spectrometry analysis to compare T and NT protein expression levels in H‐HCA, IHCA, b‐HCA, UHCA, and focal nodular hyperplasia. Using this methodology, we searched for proteins which are specifically deregulated in UHCA. We demonstrate that proteomic profiles allow for discriminating known HCA subtypes through identification of classical biomarkers in each HCA subgroup. We observed specific up‐regulation of the arginine synthesis pathway associated with overexpression of argininosuccinate synthase (ASS1) and arginosuccinate lyase in UHCA. ASS1 immunohistochemistry identified all the UHCA, of which 64.7% presented clinical bleeding manifestations. Interestingly, we demonstrated that the significance of ASS1 was not restricted to UHCA, but also encompassed certain hemorrhagic cases in other HCA subtypes, particularly IHCA. Conclusion: ASS1 + HCA combined with a typical hematoxylin and eosin stain aspect defined a new HCA subgroup at a high risk of bleeding. (Hepatology 2017;66:2016–2028)